Integration of multiple-omics data to reveal the shared genetic architecture of educational attainment, intelligence, cognitive performance, and Alzheimer’s disease - Wang, Fuxu; Wang, Haoyan; Yuan, Ye; Han, Bing; Qiu, Shizheng; Hu, Yang; Zang, Tianyi (Frontiers in Genetics, 2023)
Growing evidence suggests the effect of educational attainment (EA) on Alzheimer's disease (AD), but less is known about the shared genetic architecture of them. Here, leveraging genome-wide association studies (GWAS) for AD (N = 21,982/41,944), EA (N = 1,131,881), cognitive performance (N = 257,828), and intelligence (N = 78,308), we investigated their causal association with linkage disequilibrium score (LDSC) and Mendelian randomization and their shared loci with conjunctional false discovery rate (conjFDR), transcriptome-wide association studies (TWAS), and colocalization. We observed significant genetic correlations of EA (rg = -0.22, P = 5.07E-05), cognitive performance (rg = -0.27, P = 2.44E-05), and intelligence (rg = -0.30, P = 3.00E-04) with AD, and a causal relationship between EA and AD (OR = 0.74, 95%CI: 0.58-0.94, P = 0.013). We identified 13 shared loci at conjFDR < 0.01, of which 5 were novel, and prioritized 3 causal genes. These findings inform early prevention strategies for AD.